All Questions Topic List
None Questions
Previous in All Question Next in All Question
Previous in None Next in None
Question Number 78456 by arkanmath7@gmail.com last updated on 17/Jan/20
fora>0andb>a+2,verifythefollwing claim: ∑n=1∞na(a+1)(a+2)...(a+n−1)b(b+1)(b+2)...(b+n−1)=a(b−1)(b−a−1)(b−a−2)
Answered by mind is power last updated on 17/Jan/20
=∑n⩾1(n+1−1)anbn=∑n⩾1(n+1)!.anbn.n!−∑n⩾1n!.ann!.bn=S an=a(a+1)...(a+n−1) 2F1(a,b,c,z)=1+∑n⩾1an.bncn.znn! =limz→1{2F1(a,2,b,z)−2F1(a,1,b,z)} wehave β(b,c−b).2F1(a,b,c,z)=∫01xb−1(1−x)c−b−1(1−zx)−adx β(b,c−b)2F1(a,b,c,1)=∫01xb−1(1−x)c−b−a−1dx ⇒β(b,c−b)2F1(a,b,c,1)=β(b,c−b−a) ⇒2F1=β(b,c−b−a)β(b,c−b)=Γ(b)Γ(c−b−a)Γ(c)Γ(c−a)Γ(b)Γ(c−b)⇔ 2F1(a,b,c,1)=Γ(c).Γ(c−a−b)Γ(c−a)Γ(c−b) 2F1(a,2,b,1)=Γ(b)Γ(b−a−2)Γ(b−a)Γ(b−2)=(b−1)(b−2)Γ(b−2)Γ(b−a−2)(b−a−1)(b−a−2)Γ(b−a−2)Γ(b−2) =(b−1)(b−2)(b−a−1)(b−a−2) 2F1(a,1,b,1)=Γ(b)Γ(b−a−1)Γ(b−a)Γ(b−1)=(b−1)Γ(b−1)Γ(b−a−1)(b−a−1)Γ(b−a−1)Γ(b−1) =b−1b−a−1 S=2F1(a,2,b,1)−2F1(a,1,b,1)= S=(b−1)(b−2)(b−a−1)(b−a−2)−b−1(b−a−1)=b−1b−a−1.(b−2b−a−2−1) =(b−1)(b−a−1)(ab−a−2)=a(b−1)(b−a−1)(b−a−2) whatiused2F1(a,b,c,z)=Σan.bncn.znn! (n+1)!=1.2......(n+2−1) n=1.2.....(n+1−1) β(x,y)=∫01tx−1.(1−t)y−1dt=Γ(x).Γ(y)Γ(x+y)
Terms of Service
Privacy Policy
Contact: info@tinkutara.com